(untitled) (Journal of Basic and Applied Sciences, 2015)
A local study was conducted to evaluate Mass Trapping Technique by using (FLYCAP®) to control Medfly Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) on peaches PrumuspersicaL. for two seasons 2010 and 2012. Low fly density was recorded during 2010 season, (50.9 fly/ trap/ week), while high fly density was recorded in 2012 season, (553.3 fly/ trap/ week). Despite the difference in fly densities in the two seasons, the efficacy of Mass Trapping Technique and dimethoate treatment didn’t change significantly where the infestation rates were 9.65% and 7.2% respectively. Statistical analysis showed no significant differences between the two treatments, while a high significant difference was recorded for the control treatment, which was 35.97%. This study proved that Mass Trapping Technique could be a good alternative tool to combat fruit fly C. capitata in our area, or it could be incorporated in any pest management programs. With Mass Trapping Technique many unwanted problems could be avoided such as environmental pollution from pesticides and preserving biodiversity and avoiding the harmful effects on predators and parasites.